Label-Free Magnetic-Field-Assisted Fabrication of Cellular Structures - Gupta, Tamaghna (My University, 2022)
Controlled cell assembly is essential for fabricating in vitro models that mimic native tissue architecture. Conventional tissue engineering techniques are time-consuming and offer limited control over the spatial organization of cells within the assembled cell aggregates. We describe a label-free, scaffold-free, rapid cell manipulation technique to assemble cells into layered aggregates. Suspensions of cells in a culture medium with higher magnetic susceptibility are seeded into wells of a 96-well plate placed on a quartet magnet array. An FDA-approved paramagnetic agent is added to the regular cell culture medium to enhance the magnetic susceptibility. The inhomogeneous magnetic field and the susceptibility difference drive cells toward the lowest magnetic field region on the well surface. Two cell types are sequentially added to the wells to form layer-on-layer aggregates within 6 h. Next, the label-free technique is extended to develop a cell migration assay. Besides being time-consuming, the traditional scratch-based cell migration assay is not reproducible, whereas the alternate physical barrier-based method is expensive. Annular aggregates of human bronchial epithelial cells (HBEC3 KT) are formed within 3 h using a coaxially arranged ring-cylinder magnet array. The effects of the paramagnetic agent on cell viability, metabolism, and transcriptional profiles are investigated. The closures of the circular cell-free areas enclosed by HBEC3 KT are analyzed at different times in response to various signaling molecules and surface conditions. Further, we demonstrate the formation of the annular aggregates on human lung fibroblast-laden collagen hydrogel surfaces. The cell-free area closures on hydrogel surfaces in response to signaling molecules are analyzed. The high reproducibility and scalability of the label-free method make it amenable for preclinical research.
Keywords: magnetic field; paramagnetism; cell migration; wound healing assay; in vitro; layer-on-layer; 3D cell culture